Adoption and Implementation of Corporate Responsibility Practices: A Proposed Framework. (September 2015) - Vidal, Natalia; Kozak, Robert A.; Hansen, Eric
Defining and implementing Corporate Responsibility can be a challenge for many businesses. The identification of patterns in the processes of adoption and implementation of Corporate Responsibility practices can help managers to administer these processes more ably. In this research note, the authors identify four factors influencing the adoption and implementation of Corporate Responsibility practices: (a) internal drivers; (b) organizational structures; (c) attributes of practice; and (d) formal processes. Results indicate that there is also a continuous improvement component, meaning that the adoption and implementation of Corporate Responsibility practices are cyclical, rather than linear, processes.